If the shoe fits eaudiobook - Murphy, Julie (Meant to Be, 2021)
"If the Shoe Fits encompasses everything I love about rom-coms. I laughed, I swooned, I smiled. Another hit for Julie Murphy!" —Colleen Hoover, #1 New York Times best-selling author of Hopeless If the shoe doesn't fit, maybe it's time to design your own. Cindy loves shoes. A well-placed bow or a chic stacked heel is her form of self-expression. As a fashion-obsessed plus-size woman, she can never find designer clothes that work on her body, but a special pair of shoes always fits just right. With a shiny new design degree but no job in sight, Cindy moves back in with her stepmother, Erica Tremaine, the executive producer of the world's biggest dating reality show. When a contestant on Before Midnight bows out at the last minute, Cindy is thrust into the spotlight. Showcasing her killer shoe collection on network TV seems like a great way to jump-start her career. And, while she's at it, why not go on a few lavish dates with an eligible suitor? But being the first and only fat contestant on Before Midnight turns her into a viral sensation—and a body-positivity icon—overnight. Even harder to believe? She can actually see herself falling for this Prince Charming. To make it to the end, despite the fans, the haters, and a house full of fellow contestants she's not sure she can trust, Cindy will have to take a leap of faith and hope her heels— and her heart—don't break in the process. Best-selling author Julie Murphy's reimagining of a beloved fairy tale is an enchanting story of self-love and believing in the happy ending each and every one of us deserves.